Convergent Validity and Test-Retest Reliability of the Unsupported Upper Limb Exercise Test in Patients with Chronic Neck Pain. Issue 4 (August 2022) - Karazeybek, Zeynep Busra; Naz, İlknur
Chronic neck pain (CNP) causes decreased functionality of the upper extremity. A standardized measurement tool is needed for evaluating upper limb capacity in patients with CNP. The unsupported upper-limb exercise test (UULEX) is a simple, inexpensive field test developed to measure peak arm exercise capacity, but there has been no report of its validity and reliability for use with patients with CNP. Our aim in this study was to determine the validity and test-retest reliability of the UULEX for this purpose. In this cross-sectional observational study, 44 patients (33 women, 11 men; M age = 37.7, SD = 13.2 years), performed the UULEX twice, within a 1-week interval for test-retest reliability as measured by the intraclass correlation coefficient (ICC). We correlated the UULEX with the Six Minute Pegboard Ring Test (6PBRT), the 30-second Push-Up Test, and the Disability of Arm, Shoulder, and Hand Questionnaire (DASH) to assess its convergent validity. The UULEX demonstrated excellent test-retest reliability with ICC = 0.97 and 0.95 for test duration and the final weight on board, respectively. We found moderate to strong correlations between the UULEX and the 6PBRT ( r = 0.844), the 30-second Push Up Test ( r = 0.741) and the DASH ( r = −0.639), and all were significant, ( p < 0.05). MDC values were determined to be 57.7 seconds for test duration and 0.22 kg for final weight on board. Thus, the UULEX test was valid and reliable for assessing upper extremity functional capacity in patients with CNP.